A Review of the Development Status of Wire Arc Additive Manufacturing Technology - Xiaoxuan Chen; Xin Shang; Zirong Zhou; Sheng-Gui Chen (Advances in Materials Science and Engineering)
The WAAM molding process is complex, and the morphology, microstructure, and mechanical properties of the printed parts are affected by multiple factors. In this study, the heat input in the process of WAAM research has made the comprehensive elaboration. The numerical simulation method is used to simulate the molten pool in the process of WAAM, and the force, heat transfer, and velocity of the molten pool are analyzed. Path planning is also an important part of WAAM research, and there are many methods for additive manufacturing path planning, all of which are aimed at improving the dimensional accuracy and performance of the printed parts. Reasonable path planning can also be used for additive components with complex shapes and structures. This study comprehensively expounds on the research on WAAM path planning by scholars in recent years.